2015
DOI: 10.1152/ajpheart.00698.2014
|View full text |Cite
|
Sign up to set email alerts
|

VEGF165Amicrosphere therapy for myocardial infarction suppresses acute cytokine release and increases microvascular density but does not improve cardiac function

Abstract: Angiogenesis induced by growth factor-releasing microspheres can be an off-the-shelf and immediate alternative to stem cell therapy for acute myocardial infarction (AMI), independent of stem cell yield and comorbidity-induced dysfunction. Reliable and prolonged local delivery of intact proteins such as VEGF is, however, notoriously difficult. Our objective was to create a platform for local angiogenesis in human-sized hearts, using polyethylene-glycol/polybutylene-terephthalate (PEG-PBT) microsphere-based VEGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Myocardial infarction was produced in 33 swine (30.5±0.3kg) as previously described [14, 24, 25]. For this purpose, swine were sedated with an intramuscular injection of midazolam (1mg/kg), ketamine (20 mg/kg) and atropine (1mg).…”
Section: Methodsmentioning
confidence: 99%
“…Myocardial infarction was produced in 33 swine (30.5±0.3kg) as previously described [14, 24, 25]. For this purpose, swine were sedated with an intramuscular injection of midazolam (1mg/kg), ketamine (20 mg/kg) and atropine (1mg).…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of the exact method used to load degradable polymers with angiogenic factors, numerous studies have shown the therapeutic efficacy of these materials. For instance, intracoronary infusion of poly(ethylene glycol-co-butylene terephthalate) microspheres that were loaded with VEGF-A 165 increased capillary density in ischemic pig heart, although they did not improve cardiac function (598). In the ischemic mouse hindlimb, PLGA scaffolds that were loaded with VEGF-A 165 released the growth factor over several weeks (551).…”
Section: Inert Carriersmentioning
confidence: 99%
“…Cardiovascular magnetic resonance (CMR) imaging has been used for flow visualization and quantification in daily clinical practice for several decades [ 1 , 2 ]. CMR is the gold standard for non-invasive quantification of left and especially right heart function and shunt fraction [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%